Clinotanypus (Clinotanypus) pinguis Loew - Saether, Ole A. (Zenodo, 2011)
Clinotanypus (Clinotanypus) pinguis (Loew) (Fig. 2 A–E) Material examined. CANADA: Manitoba, Lake Winnipeg, Beaver Creek, emergence trap, 1 male, 21.vi. 1969; Narrows, 3 larvae, 9.vii. –10.ix.1969. To the description of the male by Roback (1971: 18) the following can be added: Anepisternum II with about 8 setae, preepisternum with about 48 setae, sensilla chaetica absent. The head capsule lengths of the Lake Winnipeg larvae are 700 µm for the fourth instar, 370–420 µm (2) for the third instars. Distribution and ecology. The species is present in small ponds, lakes and rivers. It seems to prefer soft mud, occasionally with some sand in shallow areas (Roback 1976: 194). It is known from Romania, Russia and Turkey, and from Manitoba and Ontario in Canada and widespread in USA (Roback 1976: 193, Oliver et al. 1990: 8; Spies 1999; Epler 2003, 2010; Caldwell 2009; Saether & Spies 2004; Ashe & O’Connor 2009: 138). Published as part of Saether, Ole A., 2011, Notes on some tanypods from Lake Winnipeg, Manitoba, Canada (Diptera: Chironomidae), pp. 26-42 in Zootaxa 3069 on page 28, DOI: 10.5281/zenodo.201708